The Effect of Entrepreneurial Orientation on MSMEs Business Performance with Technology Adoption as A Mediation Variable (A Study of UMKM in the Culinary Sector in Benowo District, Surabaya City) - Lailatus Sholikha; Eko Wahjudi (STKIP Taman Siswa Bima, 2025)
Developments in the current digital era have encouraged MSMEs, particularly in the culinary sector, to increase their competitiveness through various innovations. However, in Benowo District, Surabaya, many MSMEs still face obstacles, including unequal technology utilization, limited product innovation, and suboptimal market access and capital. These issues hinder MSME business performance and impact competitiveness. This study focuses on analyzing the relationship between entrepreneurial orientation and MSME business performance, considering technology adoption as a mediating variable. This study employed a quantitative approach with an explanatory design. Data were collected through a questionnaire and analyzed using the WarpPLS application. The analysis shows that entrepreneurial orientation and technology adoption have a significant and positive effect on MSME business performance. Furthermore, entrepreneurial orientation also has a significant and positive effect on technology adoption. Furthermore, technology adoption has been shown to significantly mediate the relationship between entrepreneurial orientation and MSME business performance. These results confirm that MSMEs with a strong entrepreneurial spirit and the ability to optimally adopt technology will have a greater opportunity to improve their business performance. Therefore, encouraging entrepreneurship and digital transformation is crucial for MSME development in the digital economy era.